STRATEGY FOR USING GEOGRAPHIC INFORMATION SYSTEMS TO IDENTIFY AND MAP RENEWABLE ENERGY RESOURCES IN THE FERGANA REGIO - Jalolova Malikaxon Mo‘minjon qizi; Oxunjonov Farruhbek Farxodjon o‘g‘li (American Journals, 2025)
This article presents a strategy for using Geographic Information Systems (GIS) to identify and map renewable energy resources in the Fergana region. Based on remote sensing (RS) data and GIS tools, the study evaluates the potential of solar and wind energy. It includes data collection, spatial analysis, site suitability assessment, and the development of mapping algorithms. The findings provide strategic insights for the development of alternative energy infrastructure in the region.
Keywords: Renewable energy, geographic information system, Fergana region, remote sensing, mapping, solar energy, wind energy.